'This nest is for all kinds of birds'? National identity questions in the refugee reception of the Reformed Church in Hungary. Issue 5 (20th October 2022) - Kóczián, Viktória
ABSTRACT: This contribution discusses how concerns over ethnic identity and solidarity shape attitudes towards migration within the Reformed Church in Hungary. Hungary faced an influx of refugees on two occasions in the 1980s and again in 2015, which the Reformed Church responded to very differently. At the end of the 1980s, the drastic deterioration of circumstances in Romania and the forced assimilation of ethnic minorities led to a wave of migration into Hungary. In response, the Reformed Church played a pioneering role in offering relief to refugees. The Church also became involved in the broader political issue of immigration by actively contributing to public debates. During the refugee crisis of 2015, the Church remained divided over the level of support it should offer to people who arrived primarily from the Middle East. Although practical assistance was offered to those in need by the Church's aid organisation, theologians and church leaders expressed fears about dangers that these refugees might pose to Hungary and to Europe's perceived Christian identity. This contribution argues that ethnic identity played both a constructive and restrictive role, and that the Church's distinct responses may be understood as deriving from its ethno-religious self-identification.